2020
DOI: 10.3390/ani10061092
|View full text |Cite
|
Sign up to set email alerts
|

Potential Causes of Increased Vocalisation in Elderly Cats with Cognitive Dysfunction Syndrome as Assessed by Their Owners

Abstract: The objectives of this study were to explore owner perception of the causes of increased vocalisation in cats diagnosed with cognitive dysfunction syndrome (CDS) and consider what impact this vocalisation may have on the cat’s household. Owners of cats diagnosed with CDS that presented with increased vocalisation were invited to complete an online survey. The survey consisted of 28 questions including the cat’s signalment, its medical history, and questions pertaining to the owner’s perception of what motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…When asked to suggest the likely main cause of their cats increased vocalisation, 41% suggested disorientation, 41% suggested attention seeking (i.e., wanting affection and attention from their owner) and 16% that their cat was looking for food. The owners also reported that 67.5% of cats were more affectionate 19 (Figure 2). These studies show that most of the behaviours detailed in the acronym DISHAAL can in themselves cause increased vocalisation; 'alteration in the Interactions between the pet and its owners', 'Anxiety' (e.g., causing attention seeking), 'spatial or temporal Disorientation' and 'deficits in Learning and memory' (e.g., causing a cat to forget that they have been fed), and 'alterations in the Sleep-wake cycle' likely to play a role in night crying.…”
Section: Behavioural Changes In Cats With Cdsmentioning
confidence: 93%
See 3 more Smart Citations
“…When asked to suggest the likely main cause of their cats increased vocalisation, 41% suggested disorientation, 41% suggested attention seeking (i.e., wanting affection and attention from their owner) and 16% that their cat was looking for food. The owners also reported that 67.5% of cats were more affectionate 19 (Figure 2). These studies show that most of the behaviours detailed in the acronym DISHAAL can in themselves cause increased vocalisation; 'alteration in the Interactions between the pet and its owners', 'Anxiety' (e.g., causing attention seeking), 'spatial or temporal Disorientation' and 'deficits in Learning and memory' (e.g., causing a cat to forget that they have been fed), and 'alterations in the Sleep-wake cycle' likely to play a role in night crying.…”
Section: Behavioural Changes In Cats With Cdsmentioning
confidence: 93%
“…Graph modified and used with permission from Sordo et al 2020 18 F I G U R E 2 Main causes of increased vocalisations in cats with CDS, as reported by their owners. Graph modified and used with permission from Cerna et al 2020 19 including a T-maze and matching tasks. The results showed an age-dependent decline in both discrimination and reversal learning*, as well as significant differences between groups during the matching tasks, suggesting that the older the cat, the more severe the cognitive decline they may develop.…”
Section: Cognitive Decline In Cats With Cdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age‐related cognitive decline is a common feature of normal ageing in people, 5,6 and has also been shown to occur in elderly domestic dogs and cats 7–14 . The clinical features of feline dementia (previously called cognitive dysfunction syndrome) include increased vocalization and other altered behaviours, plus a decline in learning, memory, sensorimotor, and perceptual skills 8,10,15,16 ; however, the detection and quantification of these findings are lacking in the clinical context 10 …”
Section: Introductionmentioning
confidence: 99%